'…POLTERN UND WÜRGEN UND DROHEN UND WÜTEN…': THE AESTHETIC PROJECT OF JOHANNES R. BECHER (1891–1958). (April 2013) - Davies, Peter
Abstract : This article examines aspects of the avant-garde poetic practice of Johannes R. Becher up to the end of the First World War. Taking issue with critical approaches that either read Becher's work with hindsight from the perspective of his later engagement with Stalinism or that interpret it in reductive biographical terms, this essay instead acknowledges the variety and originality of Becher's poetic project. It explores aspects of Becher's self-presentation as 'Dichter' in this period, as well as his radical demolition and reconstruction of the humanist tradition.